Pelatihan Optimalisasi Rebranding dan Digital Marketing Sebagai Upaya Penguatan UMKM Kedai Kopi Abah di Kecamatan Kepanjenkidul Kota Blitar - Chrystia Aji Putra; Roziana Febrianita; Latif Ahmad Fauzan (Lembaga Pengembangan Kinerja Dosen, 2024)
Kedai Kopi Abah is one of the SMEs that has good business development potensial in Blitar City because it has a strategic location in the middle of the busy center of Blitar City. However, there are challenge that must be faced by Kedai Kopi Abah namely that the use of social media as a digital marketing platform is still not optimal. This Community Service Program was conducted using training and socialization methods aimed directly at managers of Kedai Kopi Abah. This training and socialization activity takes the form of optimizing rebranding and strengthening digital marketing communications at Kedai Kopi Abah with the aim of improving the skills of Kedai Kopi Abah managers in producing interesting content on Instagram account. This training activity can attract a positive response from participants who attended the training and socialization on optimizing rebranding and strengthening digital marketing communication at Kedai Kopi Abah.